Historic evolutions of the effects of the European Union political instruments in the Romanian legal order – effects of the mechanism for cooperation and verification - Emilian Ciongaru (Juridical Tribune, 2016)
Since the accession of Romanian to the European Union, many unsolved problems related to the accountability and efficiency of the legal system and of the law enforcement bodies have been identified, a reason for which the European Commission justified the institution of a Mechanism for Cooperation and Verification as a political instrument for the monitoring and optimization of the progresses made by Romania to attain certain reference objectives specific to the field of reform of the legal system and the fight against corruption. This mechanism has been instituted to improve the functioning of the legislative, administrative and legal system and to repair the serious deficiencies in the fight against corruption. The goal of the mechanism for cooperation and verification was and is to ensure the adoption of those measures that may guarantee the Romanians and other member states that the administrative and judiciary decisions, standards and practices in Romania meet those of the European Union. The progresses made in the field of reform of the legal system and the fight against corruption will allow Romanian citizens and trading companies to enjoy their rights in quality of citizens of the European Union.